Case reportsST-elevation acute coronary syndrome in a patient after heart transplant - Browarek, Aldona; Dębski, Artur; Tyczyński, Paweł; Piotrowska, Małgorzata; Zieliński, Tomasz; Sobieszczańska-Małek, Małgorzata; Karcz, Maciej; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
The accelerated process of vasculopathy in heart transplant (HTx) recipients is a well-known factor of increased morbidity and mortality among this subset of patients. Heart transplant patients with acute coronary syndrome (ACS) usually do not present with typical symptoms. ST elevation (STE) is a very rare presentation of ACS in HTx recipients. We report a case of a female HTx patient, in whom STE-ACS was diagnosed and was subsequently treated with primary percutaneous coronary intervention.